Islam Dan Negara : Transformasi Pemikiran dan Praktik Politik Islam di Indonesia - EFFENDIE, Bachtiar (Paramadina, 1998)
Islam dan Negara : Transformasi Pemikiran dan Praktik Politik Islam di Indonesia